INTERAKSI ORANGTUA DAN GURU DALAM MENGENDALIKAN EMOSIONAL SISWA DI SEKOLAH DASAR EL HAQQA QURANIC SCHOOL PEKANBARU - Nikmah, Nikmah; Amin, Muhammad (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
The purpose of this study was to examine and analyze the Interaction of Parents and Teachers in Controlling Students' Emotions at El Haqqa Quranic School Elementary School, Pekanbaru. This study was conducted with a qualitative approach, using data collection methods through interviews, observations, and documentation. The subjects of the study included the Principal, Vice Principal for Curriculum, class teachers, parents, and students. Meanwhile, the object of the study was El Haqqa Quranic School Elementary School, Pekanbaru. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions or verification. The results of the study revealed that the forms of Parent and Teacher Interaction in Controlling Students' Emissal at El Haqqa Quranic School Elementary School, Pekanbaru, namely social interaction is a relationship between two or more individuals, which can influence, change, or improve the behavior of other individuals. The forms of interaction used are 1) Individual Parenting; 2) Classical Parenting; 3) Parental Visits When Report Cards are Distributed; 4) Whatsapp Group; Use of Student Books. Supporting factors for interaction between parents and teachers in controlling students' emotions at El Haqqa Quranic School Elementary School Pekanbaru are two factors, namely: 1) Supportive School Community, 2) Available Facilities and Infrastructure. While Inhibiting Factors are divided into two, namely: 1) Internal factors in the form of intelligence levels and emotional stability of students themselves are generally different; 2) External factors in the form of some parents who are still not aware of the importance of responsibility as parents to form stable and controlled student emotions. ABSTRAKTujuan dari penelitian ini adalah untuk mengkaji dan menganalisis Interaksi Orangtua dan Guru Dalam Mengendalikan Emosional Siswa di Sekolah Dasar El Haqqa Quranic School Pekanbaru. Penelitian ini dilakukan dengan pendekatan kualitatif, menggunakan metode pengumpulan data melalui wawancara, observasi, dan dokumentasi. Subjek penelitian meliputi Kepala Sekolah, Wakil Kepala Sekolah bagian Kurikulum, guru kelas, orang tua, dan siswa. Sementara itu, objek penelitian adalah Sekolah Dasar El Haqqa Quranic School Pekanbaru. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Hasil penelitian mengungkapkan bahwa bentuk-Bentuk Interaksi Orangtua dan Guru dalam Mengendalikan Emisinal Siswa di Sekolah Dasar El Haqqa Quranic School Pekanbaru yaitu interaksi sosial adalah suatu hubungan antara dua atau lebih individu, yang dapat mempengaruhi, mengubah, atau memperbaiki kelakuan individu yang lainnya. Adapun bentuk-bentuk interaksi yang digunakan yaitu 1) Individual Parenting; 2) Classical Prenting; 3) Kujunjungan Orangtua Ketika Pembagian Rapor; 4) Whatsapp Group; Penggunaan Student Book. Faktor pendukung interaksi antara orangtua dan guru dalam mengendalikan emeosional siswa di Sekolah Dasar El Haqqa Quranic School Pekanbaru terdapat dua faktor yaitu: 1) Masyarakat Sekolah Yang Mendukung, 2) Sarana dan Prasarana Yang Tersedia. Sedangkan Faktor Penghambat terbagi menjadi dua yakni: 1) Faktor internal berupa tingkat  kecerdasan dan kestabilan emosional dari siswa sendiri pada umumnya berbeda beda; 2) Faktor eksternal berupa masih ada beberapa orangtua yang belum sadar akan pentingnya tanggung jawab sebagai orangtua untuk membentuk emosional siswa yang stabil dan   terkendali.